An Innovative Telemedicine Initiative From Sri Lanka: The Value of Volunteerism in a Resource-Constrained Scenario During the COVID-19 Pandemic. (July 2022) - Karunathilake, Indika; Edirisinghe, Sajith; Weerasinghe, Manuj; Perera, B. J. C.; Hamdani, Anver; Mudiyanse, Rasnayaka; Randenikumara, Sanka; de Silva, Dulmini; Senanayake, Dulanja; Gamini De Silva, Sarath; Guruge, Kalyani; Ragunathan, M. K.; et al.
The unprecedented rise in COVID-19 cases in Sri Lanka since July 2021 led to a situation where the health system was getting overwhelmed. The priority shifted toward triaging patients and identifying those who need immediate medical intervention and managing the rest in home settings. An integrated patient management system where patients could access a medical professional through a short messages service (SMS) and calling system was established. This service provided telephone triage, patient advice, and coordinated with the national ambulance system to evacuate ill patients. This integrated helpline system had a major impact on the management of the recent surge of COVID-19 pandemic in Sri Lanka by patients needing urgent care were directed for hospitalization and the rest managed at home with support, reassurance, and guidance. The numbers of oxygen-dependent patients and deaths declined rapidly and the number of available beds increased. The system played a major role in bringing the crisis under control. Despite many challenges, this innovative integrated system is a unique example of medical volunteerism. The pandemic catalyzed the utilization of information and communication technologies effectively by providing healthcare with a reduction of the burden on healthcare institutions and professionals.